The socialpsychology of Islamist terror - interdisciplinary perspectives on violence and ISIS totalitarian structures - Jan Ilhan Kizilhan; Florian Steger (Taylor & Francis Group, 2021)
The number of potential Islamist perpetrators and supporters has been rising worldwide since the beginning of ISIS in 2014. Despite its military defeat in 2017, ISIS remains a serious threat. How come that numerous people join ISIS and allow the organisation to motivate them to participate in cruel and inhuman acts, such as mass-killings, within a very short period of time? This article offers socio-psychological explanations, such as processes like dehumanisation and role distance and the perception of a collective humiliation as well as structural and personal violence in the Middle East to answer this question. In connection to that, the authors argue that ISIS targetly addresses the psychological needs resulting from the social and political contexts in which the recruits live by having construced a distinct totalitarian ideology based on a very selective reading of religious narratives from Islam. Identifying religious elements from Islam as means for a particular purpose and not as the actual focus, the authors emphasise that ISIS has not lived another version of Islam but constructed a distinct ideology, which becomes manifest in strong internal social hierarchies, the genocide of minority groups and a dissemination of this mentality which is independent of a centralised organisation. Future studies must examine these observations and focus on the questions whether this mentality spread by ISIS changes the societies from which people are recruited and, if so, in which way this change becomes evident.